(untitled) (Research, Society and Development, 2024)
This study aimed to analyze the Body Mass Index (BMI) and the importance of school Physical Education in preventing obesity and overweight, as well as the involvement of students in physical activities outside the school context. This study adopted a descriptive, quantitative approach, utilizing a cross-sectional survey to develop the proposed objectives, calculated using the Chi-square Test and the Student’s t-test. The main results indicate that most students have a normal weight, although obesity is more prevalent at I.E.E. Assis Brasil; moreover, 98% of the students regularly engage in physical activities outside of school and recognize the importance of Physical Education for healthy habits and obesity prevention. The theoretical contribution was made through the expansion of the addressed concepts from a perspective of complementarity. The practical contribution was manifested through the discovery of empirical evidence with the potential to assist teaching practices and awareness. It is concluded that Physical Education plays a crucial role in promoting healthy habits and preventing obesity and overweight among students. The data reinforce the need for educational policies that encourage the regular practice of physical activities and awareness of healthy eating habits from childhood.